Analisis Social Media Marketing dan Sales Promotion Terhadap Minat Beli UMKM Sweet Ice - Winanda Ayu Risma Maulida; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The development of technology and social media has accelerated rapidly, it is not wrong if this condition is an opportunity for business actors to use it as a marketing medium for their business products to reach more consumers. Sweet Ice Tempuran is an MSME in the culinary sector that implements social media platforms as an effort to attract and reach more consumers. This study intends to analyze the influence of social media marketing and sales promotion on purchasing interest. This study involved 96 consumers from MSME Sweet Ice. The data collection technique used was through the use of a questionnaire; and data analysis was carried out by applying hypothesis testing using multiple regression analysis with the help of SPSS 25.0. The results of this study show that partially, the variables social media marketing (X1) and sales promotion (X2) have a positive and significant influence on purchase interest (Y). And simultaneously the variables social media marketing (X1) and sales promotion (X2) have a significant effect on purchase interest (Y) by 52.6%, while other results are influenced by other variables.